Tax treaty entitlement - Lang, Michael, 1965-; Pistone, Pasquale; Rust, Alexander; Schuch, Josef; Staringer, Claus (WU Institute for Austrian and International Tax Law European and international tax law and policy series, 2019)
"The entitlement to tax treaty benefits is of pivotal importance for taxpayers in order to obtain treaty benefits. However, the application and interpretation of the respective tax treaty provisions are not always straightforward and may often raise various questions. This is all the more true now that the OECD has introduced a number of new provisions regarding the entitlement to tax treaties into its Model Convention as part of the BEPS Project."--Page four of cover